Administrasi Pendidikan dalam Perspektif Islam: Telaah Konseptual atas Prinsip, Fungsi, dan Ruang Lingkup - Tarno; Meti Fatimah (TSAQOFAH, 2026)
Education is a crucial aspect of character formation and the improvement of human resource quality, whose success is greatly influenced by a planned and well-directed administrative system. In the context of Islamic education, administration encompasses not only managerial and technical activities but also a trust that embodies spiritual and moral values derived from the Qur’an and Hadith. This study aimed to analyze the concepts, principles, objectives, functions, scope, challenges, and development strategies of educational administration from an Islamic perspective in the modern era. The study employed a descriptive qualitative approach using a literature review method through the examination of various relevant sources. The findings showed that Islamic educational administration is the process of managing all educational components based on the principles of trustworthiness, justice, consultation, transparency, accountability, effectiveness, and efficiency. The objectives of Islamic educational administration are oriented not only toward academic achievement but also toward the holistic development of students’ potential, encompassing spiritual, intellectual, moral, social, and physical aspects, to cultivate noble character and create an Islamic learning environment. Its scope includes the management of curricula, students, educators, finances, facilities and infrastructure, and relationships between educational institutions and the community, supported by leadership with integrity. In the modern era, Islamic educational institutions face challenges arising from digital technological developments, global competition, sociocultural changes, and limited human resources. This study concludes that Islamic educational administration can be strengthened through the use of information technology, the enhancement of educators’ competencies, the reinforcement of an Islamic work culture, transparency in financial management, and the development of synergy between educational institutions and the community. These findings contribute to the development of Islamic educational governance that is adaptive to changing times without neglecting the spiritual and moral values that underpin its management.